Morphological Seed Traits and Germination of Six Species of Pachycereeae (Cactaceae) - Loza-Cornejo, Sofía; López-Mata, Lauro; Terrazas, Teresa (Journal of the Professional Association for Cactus Development, 2008)
Morphological seed traits and germination responses of freshly matured seeds of six species of Pachycereeae: Escontria chiotilla, Myrtillocactus geometrizans, Neobuxbaumia mezcalaensis, N. multiareolata, Pachycereus grandis, and Stenocereus queretaroensis were studied at room temperature in laboratory conditions with the hypothesis that seed size affects germination. Seeds are different in shape and testa structure. Both, number of seeds per fruit and seed traits (length, width, width/length ratio, and mass) showed statistically significant differences. The highest correlation coefficients corresponded to seed length and width, length and mass, and width and mass. Seed germination started 3-6 days after sowing in those species with larger size and mass, whereas the smaller and lighter seeds of E. chiotilla and M. geometrizans required 15 days suggesting a delay in germination, thus seeds were nondormant. Seed size and germination response differences agree with hypothesis of appertaining to different phylogenetic clades.